Analysis of the main provisions of the article LS-722 ‛‛Microbiocenosis of Anthropogenically Transformed Soils” - Maxim Viktorovich Larionov (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2022)
Relevance of the topic: Soils are complex bio-inert systems. The biological component in them is a factor of resource value and stability of soil ecosystems. The authors have chosen interesting objects for research from the point of view of soil science, soil biology and oxicology. The study of microbiocenoses in soils is always relevant. Since it is a complex biological marker of geochemical processes and stability. In view of the significant variability of the pedosphere and directly soil biota, the study of representatives of the microbiota is an important area in soil science. And this is at any time. In addition, this study can be a scientific basis for soil bioremediation directly within the framework of environmental design in the territories of treatment facilities and other technospheric facilities.